Ultrasound findings of fibroepithelial polyp in the fetal bladder: a case report - Chen, Xin; Luo, Hong (Frontiers in Oncology, 2024)
Fibroepithelial polyps are rare benign tumors originating from the mesoderm and are more commonly found in the renal pelvis and distal ureter and less frequently in the proximal ureter or bladder. This case report presents a fibroepithelial polyp occurring in the bladder of the fetus, showcasing its two-dimensional ultrasound, three-dimensional ultrasound, color Doppler, and spectral Doppler ultrasound findings, providing a reference for the accurate diagnosis of this condition.